SUBFRAME STRUCTURAL STRENGTH AND MODAL ANALYSIS OF A CAR AND STRUCTURE MODIFICATION - PAN Yu (Jixie qiangdu)
For a vehicle subframe appear crack problem in rig test process,using finite element analysis software Hyper Mesh establish the finite element model,of subframe,it analysis the strength and modal of subframe,and finite element analysis results are verified by fatigue bench test,results showed that cracking position is basically the same with finite element analysis,and put forward some improvement methods,stress of the improved subframe decreased significantly and the subframe completes the fatigue rig test.